PREVENIREA INFRACȚIUNILOR INFORMATICE CA FUNDAMENT PENTRU GARANTAREA SECURITĂȚII NAȚIONALE - Bencheci, Marcel; Panfilii, Nicolae; Hîrbu, Diana (CEP USM, 2024)
Preventing cybercrimes is essential for maintaining national security in an increasingly digitalized world. The use of cutting-edge technologies, such as artificial intelligence and intrusion detection systems, is crucial for protecting critical infrastructure. Additionally, updating laws in this field and enforcing strict regulations are essential for deterring and sanctioning cybercrimes. International cooperation on legislation can also improve the efficiency of prevention and combat measures. Raising awareness of risks and protective measures among citizens and employees can prevent many cyberattacks, and cybersecurity awareness and training programs should be prioritized to reduce vulnerabilities. By adopting these measures, cybercrime prevention can become a fundamental pillar of national security, protecting critical infrastructure and ensuring national stability and safety.
PREVENTING CYBERCRIMES AS A FOUNDATION FOR ENSURING NATIONAL SECURITY
Keywords: security threats; cybercrime; Republic of Moldova; state; national security